ONOMATOPOEIA IN AVATAR â€œTHE LAST AIR BENDER NORTH AND SOUTHâ€ - Kadek Bara Dwipayana; Putu Desi Anggerina Hikmaharyanti (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
Comic is an image juxtaposed with other images in a sequence and make a story. The onomatopoeia word is used to build a story as well as for visual effects in comic stories. This study investigated onomatopoeia emerged in Avatar â€œThe Last Air Bander-North and Southâ€ Comic Chapter 1. This study applied descriptive qualitative method. The data collection was carried out by using the observation through several stages, such as reading comics, highlighting the onomatopoeia found in comic, classifying onomatopoeia according to its type, and analyzing the meaning of onomatopoeia. This study used the theory from Bredin (1996) to determine the type of onomatopoeic word. On the other hand, the meaning of onomatopoeic words was analyzed using the theory from Thomas (1995). The results of this study indicated that three types of onomatopoeia found in comics, they were 32 (76%) direct onomatopoeia, 2 (5%) associative onomatopoeia, and 8 (19%) exemplary onomatopoeia. The meaning of onomatopoeic words contained in comics was included in abstract and contextual meaning.